Penentuan Faktor Resiko Kejadian Bayi Berat Lahir Rendah di Padang SUmatera Barat Menggunakan Analisis Regresi Logistik - Hazmira Yozza; Ferra Yanuar; Izzati Rahmi; Nadya Putri Alisya (Jurnal Matematika MANTIK, 2020)
Infant mortality is one of the indicators used to measure the quality of life of a nation. The World Health Organization (WHO) stated that one of the main causes of infant mortality is the low birth weight (LBW). Efforts to reduce the incidence of LBW can be done by monitoring risk factors that influence the occurrence of LBW in the prenatal phase. This study aims to identify factors that significantly influence the incidence of LBW babies in Padang, West Sumatra, Indonesia. The analysis was carried out by using Logistic Regression Analysis on the data of maternal births domiciled in Padang, West Sumatra, Indonesia. It was concluded that variables that significantly affect the incidence of LBW are maternal weight, parity, distance from a previous birth, problems during pregnancy, and babies’ gender.